Identification of Five Cytotoxicity-Related Genes Involved in the Progression of Triple-Negative Breast Cancer - Zhang, Yan; Tong, Gui-hui; Wei, Xu-Xuan; Chen, Hai-yang; Liang, Tian; Tang, Hong-Ping; Wu, Chuan-An; Wen, Guo-Ming; Yang, Wei-Kang; Liang, Li; Shen, Hong (Frontiers in Genetics, 2022)
Background: Breast cancer is one of the deadly tumors in women, and its incidence continues to increase. This study aimed to identify novel therapeutic molecules using RNA sequencing (RNAseq) data of breast cancer from our hospitals. Methods: 30 pairs of normal and cancerous tissues were collected and RNA sequenced in our medical center. Differentially expressed genes (DEGs) were calculated with raw data by the R package "edgeR", and functionally annotated using R package “clusterProfiler”. Tumor-infiltrating immune cells (TIICs) were estimated using a website tool TIMER 2.0. Effects of key gens on therapeutic efficacy were analyzed using RNAseq data and drug sensitivity data from two databases: the Cancer Cell Line Encyclopedia (CCLE) and the Cancer Therapeutics Response Portal (CTRP). Results: There were 2953 DEGs between normal and cancerous tissues, as well as 975 DEGs between cancerous tissues with lymph node metastasis and those with negative lymph node metastasis. These genes were primarily enriched in PI3K-Akt signaling pathway, calcium signaling pathway, cAMP signaling pathway, and cell cycle. Notably, CD8+ T cell, M0 macrophage, M1 macrophage, regulatory T cell and follicular helper T cell were significantly elevated in cancerous tissue compared with normal tissue. Eventually, we found five genes (GALNTL5, MLIP, HMCN2, LRRN4CL, DUOX2) were markedly corelated with CD8+ T cell infiltration and cytotoxicity, and associated with therapeutic response. Conclusion: We found five key gens associated with tumor progression, CD8+ T cell and therapeutic efficacy. The findings would provide potential molecular targets for the treatment of breast cancer.